2019
DOI: 10.1016/j.pedneo.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of atopic dermatitis in 6–8 year-old first graders in Taipei

Abstract: Our study verified personal and environmental risk factors of AD in children in Taiwan. Based on the results, we propose that avoiding bronchiolitis before the age of two, using antibiotics properly in babies, and providing diet counseling for breastfeeding mothers may be good prevention strategies of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Our multivariate analysis also revealed that Pohang-Si had higher odds ratios of AD and AR than Yeongdeok-Gun. In fact, several studies conducted in developed countries have shown a higher prevalence of allergic diseases [12,21,22,23,24], and in another, urban areas were found to be more prone to allergic diseases [25], which supports the argument that industrialization is associated with the higher prevalence of allergic diseases.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our multivariate analysis also revealed that Pohang-Si had higher odds ratios of AD and AR than Yeongdeok-Gun. In fact, several studies conducted in developed countries have shown a higher prevalence of allergic diseases [12,21,22,23,24], and in another, urban areas were found to be more prone to allergic diseases [25], which supports the argument that industrialization is associated with the higher prevalence of allergic diseases.…”
Section: Discussionmentioning
confidence: 64%
“…Views differ regarding whether age is a risk factor of allergic diseases [26,27]. One study [21] demonstrated a weak relation between age and allergic diseases, whereas another study [22] found a positive association. In the present study, those aged ≥19 had higher odds for AD and AR, possibly because our subjects were more exposed to allergens because this population may be more ambulatory, socio-economically active and might encounter more chances of being exposed to allergens during work and travel compared to the lower age group population.…”
Section: Discussionmentioning
confidence: 99%
“…RNN/5/15/KE. czynniki, jak brak zachorowania na zapalenie oskrzelików przed ukończeniem 2. roku życia, prawidłowe stosowanie antybiotyków u niemowląt i porady dietetyczne dla matek karmiących piersią [7]. W patogenezie AZS mutacje w genach kodujących białka strukturalne warstwy rogowej naskórka wpływają na funkcję bariery naskórkowej, natomiast stan zapalny rozwija się jako skutek kaskady cytokinowej związanej ze zmianami bariery [8].…”
Section: Methodsunclassified
“…Dermatology Review/Przegląd Dermatologiczny 2019/3 breastfeeding mothers may be good prevention strategies of AD [7]. In the pathogenesis of AD mutations in genes encoding stratum corneum structural proteins impact epidermal barrier function, while inflammation emerges as a downstream consequence of a sustained, barrier-driven cytokine cascade [8].…”
Section: Wprowadzeniementioning
confidence: 99%
“…In Taiwan, 24,999 Taiwanese children between 6–8-years of age were studied. The reported AD period prevalence within the time period of 2007 to 2008 was 10.7% [ 75 ]. Lin et al conducted a study among 74,688 junior high school students within the age range of 13 to 15 years old, which gave a prevalence of 7.6% [ 48 ].…”
Section: Global Epidemiology Of Admentioning
confidence: 99%